Ocular Pathology and Occasionally Detectable Intraocular Severe Acute Respiratory Syndrome Coronavirus-2 RNA in Five Fatal Coronavirus Disease-19 Cases - Reinhold, Aja; Tzankov, Alexandar; Matter, Matthias S.; Mihic-Probst, Daniela; Scholl, Hendrik P.N.; Meyer, Peter (Ophthalmic research, 2021)
Introduction: In December 2019, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic broke out. The virus rapidly spread globally, resulting in a major world public-health crisis. The major disease manifestation occurs in the respiratory tract. However, further studies documented other systemic involvement. This study investigates histopathologic eye changes in postmortem material of coronavirus disease 2019 (COVID-19) patients. Methods: Sections of formalin-fixed, paraffin-embedded eyes from 5 patients (10 eyes) who died of COVID-19 at the University Hospital in Basel were included. Gross examination and histological evaluation were performed by 3 independent ophthalmopathologists. Immunohistochemical staining was performed using antibodies against fibrin, cleaved caspase 3, and ACE-2. Five enucleated eyes of patients not infected with SARS-CoV-2 served as control group. All cases have been studied for presence of SARS-CoV-2 RNA by means of reverse transcription PCR and RNA in situ hybridization (ISH). The choroidal vessels of one case were analyzed with electron microscope. Results: Ophthalmopathologically, 8 eyes from 4 patients displayed swollen endothelial cells in congested choroidal vessels. No further evidence of specific eye involvement of SARS-CoV-2 was found in any of the patients. In the 8 eyes with evidence of changes due to SARS-CoV-2, immunohistochemical staining demonstrated fibrin microthrombi, apoptotic changes of endothelial and inflammatory cells. In control eyes, ACE-2 was detectable in the conjunctiva, cornea, retina, and choroidea and displayed significantly lower amounts of stained cells as in COVID-19 eyes. SARS-CoV-2 RNA was detectable in both bulbi of 2/5 patients, yet ISH failed to visualize viruses. Electron microscopy showed no significant results due to the artifacts. Discussion/Conclusion: As already described in other organs of COVID-19 patients, the ophthalmological examination revealed-microthrombi, that is, hypercoagulation and vasculopathy most probably due to endothelial damage. A possible viral spread to the endothelial cells via ACE-2 provides one pathophysiological explanation. The expression of ACE-2 receptors in the conjunctiva hints toward its susceptibility to infection. To what extend eyes, function is disrupted by SARS-CoV-2 is subject to further studies, especially in the clinic.